FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MASYARAKAT TERHADAP PROTOCOL KESEHATAN COVID-19 DI KELURAHAN PANGOLOMBIAN KECAMATAN TOMOHON SELATAN KOTA TOMOHON - Lumowa, Silvana Jinny Damaris; Bawiling, Nancy; Mamuaja, Prycilia P. (Yayasan Syalom Cipta Sumikolah, 2024)
Background: The Covid-19 (Coronavirus Disease-2019) pandemic caused by the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) virus is an event that threatens public health in general and has attracted world attention. For data on positive Covid-19 sufferers in Pangolombian subdistrict, based on data from the Pangolombian subdistrict health center, there were 58 cases, 57 people recovered and 1 person died. Objective: To find out the factors that influence community compliance with the Covid-19 Health Protocol in Pangolombian Village, South Tomohon District, Tomohon City. Methodology: This research uses quantitative methods with an analytical survey design with a cross sectional study design which was conducted in February 2022. Sampling used Non Probability Sampling, namely